2016
DOI: 10.1080/10803548.2016.1181484
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a cooling jacket with reference to physiological responses in iron foundry workers

Abstract: Personal cooling garments (PCGs) have gained increased attention in recent years due to heat stress and strain in the working environment. The present study was conducted in hot environments of an iron foundry to evaluate the efficacy of a battery-operated PCG. Twenty-four workers were exposed to climatic conditions of 35.89 ± 1.25 °C, 35% relative humidity during 90-min work with PCG and habitual clothing (HC). Mean weighted skin temperature was significantly lower by 4.84 ± 1.05 °C compared with HC 0.38 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…In contrast, four of the 16 studies at worksites examined cooling interventions on one to four workdays. Among the agricultural, construction, and industrial cooling interventions studies, five of the trials were 2 h or less 24‐28 . Due to the nature of the extreme heat exposure (82–309°C) firefighters encounter, those trials were less than 2 h.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, four of the 16 studies at worksites examined cooling interventions on one to four workdays. Among the agricultural, construction, and industrial cooling interventions studies, five of the trials were 2 h or less 24‐28 . Due to the nature of the extreme heat exposure (82–309°C) firefighters encounter, those trials were less than 2 h.…”
Section: Resultsmentioning
confidence: 99%
“…Among the agricultural, construction, and industrial worker cooling interventions studies, 41% of the trials were 2 h or less. [24][25][26][27][28] Working More female participants are needed in occupational cooling studies in light of changing demographics of the outdoor occupational sectors that have led to increased workforce diversity. 44,45 In addition, there are sex-related differences in heat stress tolerance and previous results have shown females report three or more symptoms more frequently than males (OR = 2.67, 95% CI, 1.1-6.6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, those required to wear full PPE in hot environments need to avoid under-hydration, overheating and fatigue. Studies have indicated that the optimization of work clothing (for example, ventilation cooling shirts [58] or garments incorporating a liquid coolant [59]) is a factor that may be of great importance for heat-stress mitigation in industrial settings where workers are exposed to elevated heat stress. Further research is required to investigate alternative fabrics suitable for PPE in hot environments and the feasibility of wearable cooling garments where possible.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor workers, such as construction workers, miners, and hot processes in iron, steel, glass and rubber foundries, firefighters who perform highly intense physical activities, are exposed to heat 3 stress, particularly in tropical and subtropical regions or countries (1)(2)(3). The combination of physical activities, high ambient temperatures and humidity may create excessive heat strain, which would effect on physical, subjective and physiological performance if preventive measures are not taken (2,4).…”
Section: Introductionmentioning
confidence: 99%